2010
DOI: 10.1080/10871201003718029
|View full text |Cite
|
Sign up to set email alerts
|

CWD After “the Fire”: Six Reasons Why Hunters Resisted Wisconsin's Eradication Effort

Abstract: Eight years after undertaking an unprecedented attempt to eradicate chronic wasting disease (CWD) from its free-ranging white-tailed deer (Odocoileus virginianus) population, Wisconsin wildlife managers are rethinking their strategies in the face of public opposition to their efforts. This article draws on a dozen surveys of hunters and landowners to identify six psychological bases that created deer hunter opposition to the Wisconsin plan. These include opposition to the population goal, conflicts with tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 14 publications
1
56
1
Order By: Relevance
“…An understanding of the human dimensions of wildlife management efforts, such as the establishment of buffers, is critical if such efforts require broad community support and acceptance to be effective. It is widely accepted that wildlife management programs, which exclude human social considerations, risk low compliance or even failure (e.g., Holsman, Petchenik, & Cooney, 2010). Thus, this study also includes human opinions of various buffer options.…”
Section: Factor Sourcementioning
confidence: 98%
“…An understanding of the human dimensions of wildlife management efforts, such as the establishment of buffers, is critical if such efforts require broad community support and acceptance to be effective. It is widely accepted that wildlife management programs, which exclude human social considerations, risk low compliance or even failure (e.g., Holsman, Petchenik, & Cooney, 2010). Thus, this study also includes human opinions of various buffer options.…”
Section: Factor Sourcementioning
confidence: 98%
“…Understanding this relationship will help guide management decisions, which is especially important in light of the public controversy over the effects of culling and other regulations intended to reduce deer populations (Holsman et al 2010). Using data on CWD-infection and deer density, we investigated whether CWD transmission in white-tailed deer is better described as frequency-dependent, density-dependent, or by an intermediate form.…”
Section: Introductionmentioning
confidence: 99%
“…Yet Peterson et al (2006) concluded that hunters would support severe deer density reductions on the basis of their study of a hypothetical disease with similar characteristics (i.e., dreadful and uncertain) to CWD (Slovic, 1987). Their conclusion appears incongruent with experiences in both Michigan and Wisconsin where broad support for disease eradication has not translated into specific support for deer herd reduction as a strategy (Dorn & Mertig, 2005;Holsman & Cooney, 2007) or widespread participation in the deer reduction effort (Holsman & Petchenik, 2006). This raises questions about the role of risk perceptions in hunter support for deer density reduction.…”
Section: Risk Perceptionsmentioning
confidence: 87%